2012
DOI: 10.1038/labinvest.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl sulfate-induced epithelial-to-mesenchymal transition and apoptosis of renal tubular cells as novel mechanisms of progression of renal disease

Abstract: Indoxyl sulfate (IS), one of the uremic toxins, is regarded to have a substantial role in the progression of chronic kidney disease (CKD). Epithelial-to-mesenchymal transition (EMT) and apoptosis of renal tubular cells are known to be the critical mechanisms of the development and aggravation of CKD. We investigated the effect of IS on EMT and apoptosis in renal proximal tubular cells, NRK-52E cells. IS significantly inhibited cell proliferation and induced cell migration with a morphological transition from c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 38 publications
(43 reference statements)
2
50
1
1
Order By: Relevance
“…The decreased cell number of podocytes following indoxyl sulfate exposure may reflect cell death or detachment from the culture substratum. In fact, apoptosis and altered adherens junctions have been reported in indoxyl sulfate-exposed endothelial cells and renal tubular cells [49], [50], and our microarray results for indoxyl sulfate-exposed human podocytes also showed decreased expression of integrins, which facilitate podocyte adhesion to the extracellular matrix [25], [39], [51].…”
Section: Discussionmentioning
confidence: 54%
“…The decreased cell number of podocytes following indoxyl sulfate exposure may reflect cell death or detachment from the culture substratum. In fact, apoptosis and altered adherens junctions have been reported in indoxyl sulfate-exposed endothelial cells and renal tubular cells [49], [50], and our microarray results for indoxyl sulfate-exposed human podocytes also showed decreased expression of integrins, which facilitate podocyte adhesion to the extracellular matrix [25], [39], [51].…”
Section: Discussionmentioning
confidence: 54%
“…38,98,99 It is well documented that several uremic toxins can induce apoptosis in a variety of cell types, such as smooth muscle cells, neutrophils, and proximal tubule cells. [100][101][102] However, only a few studies have reported a direct effect of uremic solutes on cell metabolism, including mitochondrial functioning. Mitochondria are Figure 3.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 99%
“…16 The filters were immersed overnight in 130 mg/ml matrigel (10 mg/ml; Becton Dickenson, Franklin Lakes, NJ, USA) in PBS at 4 1C. The HPMCs were seeded onto the top of the transwell filter with the addition of DEXA (10 mM) to the lower chamber under serum-free conditions.…”
Section: Cell Migration Assaymentioning
confidence: 99%